Properties of bitumen modified with latex. (May 2019) - Daniel, N. H.; Hassan, N. A.; Idham, M. K.; Jaya, R. P.; Hainin, M. R.; Ismail, C. R.; Puan, O. C.; Azahar, N. M.
Abstract: A lot of effort has been made to improve the base bitumen properties by adding different types of modifier. The current issue of pavement failure has raised a concern that high specification of bitumen is essential to counter the asphalt pavement challenges. This is to ensure that the bitumen could perform better as a road material. Natural rubber, particularly latex, has potential to be used as a modifier in bitumen compared to other types of rubber as it is cheaper, accessible and easily dispersed in the liquid bitumen when heated. This study evaluates the physical and rheological properties of the bitumen when added with latex rubber. Difference percentages of latex i.e. 2.5%, 5.0%, 7.5% and 10% were added to the 60/70 PEN bitumen and tested for penetration, softening point, viscosity, ductility, loss on heating and dynamic shear rheometer tests. As a result of the modification, it was found that latex hardened the control bitumen, increases the viscosity and provides better resistance against rutting.